2015
DOI: 10.1007/s40195-015-0270-4
|View full text |Cite
|
Sign up to set email alerts
|

A New Understanding of Stress Corrosion Cracking Mechanism of X80 Pipeline Steel at Passive Potential in High-pH Solutions

Abstract: Susceptibilities to stress corrosion cracking (SCC) of X80 pipeline steel in relatively concentrated carbonate/ bicarbonate solutions with different chloride ion concentrations or pH value at a passive potential of -200 mV vs SCE were investigated by slow strain rate tensile test. In order to explore the SCC mechanism and the evaluation criterion for the SCC susceptibility of the steel in passive state, electrochemical measurements were taken. Potentiodynamic polarization curves were obtained at different pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…It is important to point out that despite that the steel exhibit a low susceptibility at these pHs, a few secondary cracks were observed close to the neck region. Similar results were reported by Fan et al [ 54 ]. In their study, an X80 steel showed a low susceptibility to SCC in a carbonate-bicarbonate solution without chloride ion, but shallow and short secondary cracks initiated on the lateral surface.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It is important to point out that despite that the steel exhibit a low susceptibility at these pHs, a few secondary cracks were observed close to the neck region. Similar results were reported by Fan et al [ 54 ]. In their study, an X80 steel showed a low susceptibility to SCC in a carbonate-bicarbonate solution without chloride ion, but shallow and short secondary cracks initiated on the lateral surface.…”
Section: Resultssupporting
confidence: 92%
“…For an approximate physical description of the EIS measurements of the steel in NS4 solution at different pH during SSRT test, equivalent electric circuits (EEC) are suggested as shown in Figure 6 . The first EEC ( Figure 6 a) was employed to fit the EIS data in the acid solution (pH 3), in which the R s is solution resistance, R ct is the charge-transfer resistance, L ads and R ads are the inductance and resistance of the adsorption process, respectively [ 22 , 54 ]. The constant phase element (CPE dl ) is an empirical circuit element that represents the non-ideal capacitive behavior of the electrode.…”
Section: Resultsmentioning
confidence: 99%
“…This new layer is not stable and starts to dissolve in high-temperature water. At some point, it loses its protective nature and oxidation starts to propagate deeper into the matrix [27][28][29]. Therefore, owning to the positive effect of Cr 2 O 3 on the SCC resistance, the TIG joint containing less Cr 2 O 3 is more vulnerable to oxide rupture and has higher SCC susceptibility in the simulated PRW environment.…”
Section: Corrosion Productsmentioning
confidence: 99%
“…The electrochemical behavior of stainless steels was studied widely, which is strongly related to chemical compositions and microstructures of stainless steels and corrosive media [27,28]. [29,30].…”
Section: The Influence Of Corrosive Media On the Surface State Of Weamentioning
confidence: 99%